Universitas di Indonesia: Apakah Sudah Siap Untuk Menyusun Laporan Keberlanjutan? - Asniati Bahari; Dwivana Asri Chasvella; Sanda Patrisia Komalasari (Politeknik Caltex Riau, 2022)
This study aims to analyze the higher education in Indonesia’s level of readiness in conducting sustainable reporting in accordance with the standards applied by the GRI (Global Reporting Initiative), which is GRI Standards. The assessment was done by looking at the percentage of suitability presented by universities on their websites with information that should be disclosed in accordance with the standards of the indicators issued by the GRI. The variables used to measure the level of readiness are in the form of disclosure items on each GRI indicator, namely indicators on disclosure of universal standards, economic standards, environmental standards, and social standards. The data used in this study are secondary data in the form of the whole available information for the public posted on the university's websites. The research object used in this study was the 35th best university according to the Ministry of Research, Technology, and Higher Education in 2019. The results of this study indicate that overall, universities in Indonesia are less prepared for universal standard disclosure indicators. For economic, environmental, and social standards indicators, universities are declared unprepared. In this case, clear guidelines are needed to be used by universities in Indonesia in preparing sustainability reports.